2019
DOI: 10.1038/s41431-019-0529-8
|View full text |Cite
|
Sign up to set email alerts
|

Public reactions to direct-to-consumer genetic health tests: A comparison across the US, UK, Japan and Australia

Abstract: collected UK and Japanese data on behalf of the Centre for Law & Genetics and Osaka University respectively. Critchley and Charbonneau prepared the initial draft with all authors contributing to the final article. Walshe programmed the survey and contributed to specific data preparation, analysis and literature review for this article. Yamamoto and Kato contributed to survey translation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…However, over recent years, the FDA has allowed the marketing of tests that provide genetic risk information for certain conditions (ten different kinds of diseases) [ 2 ]. At present, the vast majority of the available literature concerning DTC-GT refers to the US context and largely reflects the perspective of people who have never purchased a DTC-GT [ 4 , 5 ], or early adopters comprising well-educated people within the scientific community (engineers, biologists, health, and technology experts) who are knowledgeable about techno-scientific innovations [ 6 8 ]. In the last 10 years, genetic tests, which are marketed directly to the community, have made their appearance worldwide, spreading to several countries and cultures and also establishing themselves among European users—who are largely different from the US “early adopters” in terms of scientific literacy and background [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, over recent years, the FDA has allowed the marketing of tests that provide genetic risk information for certain conditions (ten different kinds of diseases) [ 2 ]. At present, the vast majority of the available literature concerning DTC-GT refers to the US context and largely reflects the perspective of people who have never purchased a DTC-GT [ 4 , 5 ], or early adopters comprising well-educated people within the scientific community (engineers, biologists, health, and technology experts) who are knowledgeable about techno-scientific innovations [ 6 8 ]. In the last 10 years, genetic tests, which are marketed directly to the community, have made their appearance worldwide, spreading to several countries and cultures and also establishing themselves among European users—who are largely different from the US “early adopters” in terms of scientific literacy and background [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…A similar context and tendency seem to characterize other European populations, such as in Greece ( 13 , 14 ), the Netherlands ( 15 ), Germany ( 16 ), or Switzerland ( 17 ). Most of the articles available in the literature concerning DTC-GT consumers are focused on countries outside the European Union (the US in particular) and investigated perspectives in laypeople or highly educated groups of graduate students who had never purchased a DTC-GT ( 18 , 19 ). Few studies reported outcomes on actual consumers in Europe.…”
Section: Introductionmentioning
confidence: 99%
“…The number of companies providing direct-to-consumer tests is growing around the world [ 43 , 110 , 111 ]. Tests for home blood collection and lab based-immunological tests (i.e., antibody tests), home-based saliva sampling for infection and genomic testing are marketed to consumers online or in stores [ 43 , 112 , 113 , 114 , 115 ].…”
Section: Resultsmentioning
confidence: 99%